MRI and Arthroscopy Correlation in the Patellofemoral Joint. Issue 4 (December 2017) - Friedman, Lisa G.M.; White, Melissa S.; Carroll, Patrick F.; Macalena, Jeffrey A.; Arendt, Elizabeth A.; Ellermann, Jutta M.; Tompkins, Marc
Abstract : The patellofemoral joint is an articulation between the patella and the femoral trochlea, which serves to increase the lever arm of the extensor mechanism. The stability of the patella within the trochlear groove is supported statically by the bony confines of the groove itself, as well as the medial patellofemoral ligament, and dynamically by the vastus musculature. Pathologic changes seen on magnetic resonance imaging (MRI) are frequently well correlated with findings found by arthroscopy at the time of surgery. Degenerative changes to the articular cartilage, osteochondral lesions and loose bodies, tears in the retinaculum, and the medial patellofemoral ligament can be seen in MRI and are well correlated with arthroscopy. In addition, other findings that may predispose an individual to injury or degenerative changes over time, such as patella alta and trochlear dysplasia, can also be assessed by MRI and observed arthroscopically. Abstract : Supplemental Digital Content is available in the text.